CTRP5-Overexpression Attenuated Ischemia-Reperfusion Associated Heart Injuries and Improved Infarction Induced Heart Failure - Peng, Meng; Liu, Yuan; Zhang, Xiang-qin; Xu, Ya-wei; Zhao, Yin-tao; Yang, Hai-bo (Frontiers in Pharmacology, 2020)
Aims: C1q/tumor necrosis factor (TNF)-related protein5 (CTRP5) belongs to the C1q/TNF-α related protein family and exhibits to regulate glucose and lipid metabolism and inflammation production. However, the roles of CTRP5 in ischemia/reperfusion (I/R) associated cardiac injuries and heart failure (HF) remains not to be reported. This study aimed to investigate the roles of CTRP5 in I/R associated cardiac injuries and HF. Materials and methods: Adeno-associated virus serum type 9 （AAV9）vectors were established for CTRP5 overexpression in mouse heart (AAV9-CTRP5 mouse). AAV9-CTRP5, AMPKα2 global knock out （AMPKα2-/-）and AAV9-CTRP5+ AMPKα2-/- mouse were used to establish cardiac I/R or infarction associated HF to investigate the roles and mechanisms of CTRP5 in vivo. Isolated neonatal rat cardiomyocytes (NRCM) transfected with or without CTRP5 was used to establish hypoxia /reoxygenation (H/O) model to study the roles and mechanisms of CTRP5 in vitro. Key findings: CTRP5 was up-regulated after MI but was quickly down-regulated. CTRP5 overexpression significantly decreased I/R induced IA/AAR and cardiomyocyte apoptosis, and significantly attenuated infarction area and improved mouse cardiac function. Mechanistically, CTRP5 overexpression markedly increased AMPKα2 and ACC phosphorylation and PGC1-α expression, but inhibited mTORC1 phosphorylation. In vitro experiments, CTRP5 overexpression could also enhance AMPKα2 and ACC phosphorylation and protect against H/O induced cardiomyocyte apoptosis. Finally, we showed that CTPR5 overexpression could not prevent I/R associated cardiac injuries and HF in AMPKα2-/- mouse. Significance: CTRP5 overexpression protected against I/R induced mouse heart injury and attenuated infarction induced mouse heart dysfunction by activating AMPKα/p-ACC/PGC1α signaling.